Патологический разум в пьесе Аси Волошиной Пациенты - Tyczko, Krzysztof (Studia Rossica Posnaniensia, 2020)
In this article Asia Voloshina’s drama Patients is analysed in the context of the pathologies the characters deal with. The inspirations of her play are described, i.e. the films and memories of Luis Buñuel as well as medical cases from the practice of Oliver Sacks. The author also refers to Dante Alighieri’s The Divine Comedy. In this perspective the analysed work is a text about fear that appears when the quest for freedom is abandoned. If in The Divine Comedy in hell and purgatory are people who are sinful and do not know Christ, in the universe of the clinic in “hell” there are all those who are afraid. Voloshina’s play constitutes one out of a number of her works concerning the social and political situation in Russia. In the play, the author points to fear as the source of the viciousness of the collective consciousness. Voloshina raises a question that is characteristic of the post-Soviet space: the characters “hide from themselves and their fate”. Voloshina, however, leads them towards it.